Indicadores relacionados à qualidade de vida e fatores de risco de professores da Universidade Estadual de Maringá-PR - Oliveira Filho, Albertino de (2009)
This research aimed to analyze indicators of the Quality Life and Risk Factor in professors from State University of Maringá (UEM). The participants were 288 active professors from UEM, of both sexes, who were teaching in graduation or master's degree and accepted to participate voluntarily of the research. The instrument was composed by social demographic information, consumption of alcohol and tobacco, practice level of physical activity and quality life, by self-administered version. The data collection was accomplished between October and December 2008. The data were analyzed using the descriptive statistics, being used of Statistical Package of Social Science 13. In a general way the results indicated that most of the professors has positive perception of their Quality life and health. The analysis of the domains of Quality life indicates more positive perceptions in the aspects which involve the domains Social Relationships, Physical and Environment; however they demonstrated negative perception in the aspects that involve the Psychological domain. In a specific way, the analysis of Quality life with independent variables indicated significant differences in the Psychological domains and Environment, with more positive perceptions in favor of those with higher economic level, as well as there was lineal association between economic level and more positive perception in the Psychological domains, Social Relationships and environment. The investigation of the risk factors appeared for the occurrence of 67,01% in the excessive consumption of alcohol and 10,42% in the habitual consumption classified as risk; 9,38% of smokers; 36,81% with weight excess; 56,95% of sedentary and less physically active. The analysis of the practice level of physical activity indicated 43,05% of physical active and very physical active, with lineal association just with the economic level, where those with larger purchasing power demonstrate larger involvement in physical activities of larger duration and intensities. The analysis of associations of practice level of physical activity with the domains of Quality life indicates that as larger the level of more positive practice of activities physics is the individual's perception on the subjects that characterize the Physical domain and the Psychological domain.